The Art of Science; An Exploration of Art Integration in a Science Classroom - Melissa M Hunkins (Middle Grades Review, 2019)
This Practitioner Perspective examined how art integration in a science classroom affects student engagement and scientific understanding. The study took place over one school year in a 7th and 8th grade science classroom, with a total of 57 students and a focus group of eleven students. Collaboratively, the science teacher and a teaching artist designed purposeful integration of art into two science units and developed a culmination project where students connected their science learning throughout the year to a self portrait. Findings indicated that art integration increased engagement and understanding and allowed students to visually express their learning. However, supports may be needed for students who may not consider themselves artists or are hesitant to participate in the art integrated activities.
Keywords: art integration; science; middle level